2017
DOI: 10.1007/s12020-017-1409-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for epithelial-mesenchymal transition in adrenocortical tumors?

Abstract: Vimentin, TWIST1, and SIP1 expressions are increased in aggressive ACT. Therefore, EMT may play a relevant role in adrenal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…In this study we investigated a series of both classical epithelial and mesenchymal markers in a large cohort of normal, benign and malignant adrenocortical tissues, and compared the expression of these markers with that in epithelial and mesenchymal control tissues. Against our hypothesis, our analysis revealed that in adrenocortical tumors EMT indicated by a more frequent occurrence of mesenchymal markers in neoplastic tissue, does not appear to play a role in tumor progression as suggested before in smaller studies [28,29]. Adrenocortical tissues do not express established epithelial markers like E-cadherin and EpCAM but express a series of "classical" mesenchymal markers like Slug and N-cadherin at similar levels as mesenchymal tissues.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study we investigated a series of both classical epithelial and mesenchymal markers in a large cohort of normal, benign and malignant adrenocortical tissues, and compared the expression of these markers with that in epithelial and mesenchymal control tissues. Against our hypothesis, our analysis revealed that in adrenocortical tumors EMT indicated by a more frequent occurrence of mesenchymal markers in neoplastic tissue, does not appear to play a role in tumor progression as suggested before in smaller studies [28,29]. Adrenocortical tissues do not express established epithelial markers like E-cadherin and EpCAM but express a series of "classical" mesenchymal markers like Slug and N-cadherin at similar levels as mesenchymal tissues.…”
Section: Discussionsupporting
confidence: 64%
“…Accordingly, adrenal tumors are also classified as carcinomas (tumors of an epithelial tissue) [26] as opposed to sarcomas (tumors of a mesenchymal tissue) [27]. Two studies have provided a first indication that adrenocortical tissues are expressing some mesenchymal markers [28,29]. However, the number of adrenocortical carcinoma tissues analyzed in these studies was low (24 cases in each study) and a correlation between EMT marker expression and clinicopathological markers indicative of tumor aggressiveness was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although their expression was inversely proportional, no association was observed between Twist1 and E-cadherin mRNA levels. These data corroborate our group's previous findings, as we demonstrated low levels of E-cadherin in all types of adrenocortical tumors through immunohistochemistry (8).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, Waldmann et al (7) reported an increased expression of Snail1, another EMT-related transcription factor, in 26 cases of ACC in comparison to 12 cases of adrenal adenomas. Recently, our group originally described that Twist1 protein expression is significantly increased in malignant adrenocortical tumors in both adult and childhood onset scenarios (8). Moreover, we found that the protein levels of the EMT marker vimentin were significantly increased in the most aggressive tumors, and that this increase was directly correlated to Twist1 expression.…”
mentioning
confidence: 57%
“…Increasing evidence suggests that the epithelial-mesenchymal transition (EMT) may participate in adrenal tumourigenesis. According to those reports, EMT markers (E−/P−/N-cadherins, vimentin, fibronectin, MMP-2/− 9 and caveolin-1), and downstream transcriptional regulators (TWIST1, SIP1, Snail, ZEB-1/− 2, Slug) were all found to be dysregulated and associated with poor prognosis [1214]. These results indicate a potential role of EMT in the development of ACC.…”
Section: Introductionmentioning
confidence: 97%